1993
DOI: 10.1149/1.2221059
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetic Field Effect on the Dynamics of the Anodic Dissolution of Copper

Abstract: In the anodie dissolution of copper into aqueous NaCI/KSCN electrolytes, the interaction of externally imposed magnetic fields with the anode potential determines the domain of oscillations. The oscillation patterns are analyzed in terms of power spectra and the theory of fractional Brownian motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…23, where the effects of Eq. (12) are included in the growth of the diffusion layer with time. In agreement with the experimental data (cf.…”
Section: B Normal Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…23, where the effects of Eq. (12) are included in the growth of the diffusion layer with time. In agreement with the experimental data (cf.…”
Section: B Normal Patternsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Much of the early work was concerned with the influence of uniform fields, applied parallel to the cathode in order to maximize the Lorentz force…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gu et al [52] showed that during the induction period the rate of copper oxide formation is proportional to B -1/4. As a result of the field, the total induction time until oscillations start increases [53]. The oscillations are destabilized due to mass transport or kinetic interactions [54,55], and a shift to more positive potentials is observed [50].…”
Section: Anodic Effectsmentioning
confidence: 99%
“…Magnetic fields often have a surprising influence on physical and chemical processes occurring in electrochemical cells. The rate of electrodeposition of metals [1][2][3], deposit morphology [4,5], hydrogen production [6,7], corrosion [8,9], rest potential [10], alloy composition [11,12], and magnetic properties [13], are all sensitive to applied magnetic field. The physical explanation is frequently magnetohydrodynamic, involving the Lorentz force [14] …”
mentioning
confidence: 99%